McKeachie's teaching tips : strategies, research, and theory for college and university teachers - Svinicki, Marilla D., 1946-; McKeachie, Wilbert James, 1921-; McKeachie, Wilbert James, 1921- (Belmont, CA : Wadsworth, Cengage Learning, 2011)
From the Publisher: This indispensable handbook provides helpful strategies for dealing with both the everyday challenges of university teaching and those that arise in efforts to maximize learning for every student. The suggested strategies are supported by research and adaptable to specific classroom situations. Rather than suggest a'set of recipes' to be followed mechanically, the book gives instructors the tools they need to deal with the ever-changing dynamics of teaching and learning
Introduction -- Countdown for course preparation -- Meeting a class for the first time -- Reading as active learning -- Facilitating discussion : posing problems, listening, questioning -- How to make lectures more effective -- Assessing, testing, and evaluating : grading is not the most important function -- Testing : the details -- Good designs for written feedback for students -- The ABCs of assigning grades -- Motivation in the college classroom -- Teaching culturally diverse students -- Dealing with student problems and problem students (there's almost always at least one!) -- Active learning : group-based learning -- Experiential learning : case-based, problem-based, and reality-based -- Using high-stakes and low-stakes writing to enhance learning -- Technology and teaching -- Teaching large classes (you can still get active learning!) -- Laboratory instruction : ensuring an active learning experience -- Teaching students how to become more strategic and self-regulated learners -- Teaching thinking -- The ethics of teaching and the teaching of ethics -- Vitality and growth throughout your teaching career
Rev. ed. of: McKeachie's teaching tips / Wilbert J. McKeachie. 2006
Author's names reversed on previous edition
Keywords: College teaching; First year teachers; Teaching